2022
DOI: 10.1186/s12913-022-07720-0
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study: comparison of public perceptions of adverse drug reaction reporting and monitoring in eastern and western China

Abstract: Background Adverse drug reactions (ADRs) cause a substantial clinical and economic burden. Spontaneous reporting of ADRs by the public is crucial. In some developed countries like the United States, Canada, consumers have been allowed to directly report ADRs, however, convenient channels for direct ADR reporting by the public are lacking in China. Objective We aimed to compare the knowledge, attitudes, and practice(KAP) regarding monitoring and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Since 9 studies were excluded due to inaccessibility of full-text, a total of 253 articles underwent to full-text analysis. This resulted in thirteen studies [ 37 49 ] meeting the inclusion criteria and were included in the review (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 9 studies were excluded due to inaccessibility of full-text, a total of 253 articles underwent to full-text analysis. This resulted in thirteen studies [ 37 49 ] meeting the inclusion criteria and were included in the review (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were conducted in Africa [ 39 , 42 44 , 50 ], 3 in Europe [ 38 , 47 , 49 ], 3 in Asia [ 37 , 41 , 46 ], 1 in Australia [ 48 ] and 1 in Canada [ 40 ]. Most of the studies (n = 8, 61.5%) were cross-sectional, with 2 [ 38 , 47 , 49 ] failing to report the study design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MeDRA (Medical Dictionary for Regulatory Activities) coding system was utilized for system organ classification of suspected adverse drug reactions 10 . The causal association was done by using Naranjo's causality assessment scale 11 Age is one of the important risk factors for the occurrence of ADR 14 . Previous studies showed that high incidence of ADR reporting in paediatric and old age patients may be due to age-related changes in pharmacokinetics and pharmacodynamics of drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Despite considerable research, there’s a notable gap in literature comparing pharmacovigilance KAP between healthcare professionals and the public within similar demographic settings, particularly in emerging areas like Yunnan ( 11 ). Addressing this gap is crucial, given the increasing ADR events in China and the need for effective pharmacovigilance mechanisms ( 12 ).…”
Section: Introductionmentioning
confidence: 99%